2020
DOI: 10.5603/cj.a2018.0109
|View full text |Cite
|
Sign up to set email alerts
|

Increased systemic arterial stiffness in patients with chronic thromboembolic pulmonary hypertension

Abstract: Background: Chronic thromboembolic pulmonary hypertension (CTEPH) is a complication of venous thromboembolism (VTE) resulting from non-dissolving thromboemboli in the pulmonary arteries. Previous observations indicate a higher prevalence of atherosclerosis and cardiovascular risk factors in patients with VTE and CTEPH. The purpose of the present study was to evaluate the arterial stiffening assessed by pulse wave velocity (PWV), a marker of arterial stiffness, in CTEPH patients in comparison with a matched con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
2
13
0
1
Order By: Relevance
“…In both indicated studies, 76 , 77 it was suggested that increased systemic arterial stiffness could be associated with poor prognosis in pulmonary hypertension, but only in the present study did we test this suggestion, and confirmed that increased CAVI is associated with a higher rate of death, independent to other traditional risk factors – OR = 1.13, CI 1.001–1.871. In non-survived patients the mean CAVI was significantly higher than in patients who survived – 7.8±1.56 vs 6.8±1.2, P = 0.004, while PWVe and PWVm did not differ significantly and were not associated with the prognosis.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In both indicated studies, 76 , 77 it was suggested that increased systemic arterial stiffness could be associated with poor prognosis in pulmonary hypertension, but only in the present study did we test this suggestion, and confirmed that increased CAVI is associated with a higher rate of death, independent to other traditional risk factors – OR = 1.13, CI 1.001–1.871. In non-survived patients the mean CAVI was significantly higher than in patients who survived – 7.8±1.56 vs 6.8±1.2, P = 0.004, while PWVe and PWVm did not differ significantly and were not associated with the prognosis.…”
Section: Discussionsupporting
confidence: 67%
“… 76 Also, in patients with chronic thromboembolic pulmonary hypertension Sznajder et al found significantly higher PWVe than in the control group which was matched to age, gender, and concomitant diseases. 77 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the authors concluded that the patients with pulmonary arterial hypertension had altered vascular function in the systemic arteries and, considering the relationship between PWV and pulmonary hypertension severity, systemic arterial stiffness might serve as a marker of the disease severity and response to a treatment. Sznajder et al 33 found the elevated PWVe was associated with older age, higher pulmonary vascular resistance and lower oxygen saturation in CTEPH.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, mean PWVe values were very similar to those in Chamorro et al's study for IPAH patients (8.49±1.92 m/s) and healthy adults (7.29±0.87 m/s). Sznajder et al 33 evaluated systemic arterial stiffness in chronic thromboembolic pulmonary hypertension (CTEPH) and the control group patients were adjusted by age, gender, and concomitant diseases. They found significantly higher levels of PWVe in CTEPH patients (10.3 ± 2.5 vs 9 ± 1.3 m/s, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation